2019
DOI: 10.1542/peds.2018-2305
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Crashes, Violations, and Suspensions Among Young Drivers With ADHD

Abstract: OBJECTIVES: To compare monthly rates of specific types of crashes, violations, and license suspensions over the first years of licensure for drivers with and without attention-deficit/ hyperactivity disorder (ADHD). METHODS:We identified patients of New Jersey primary care locations of the Children's Hospital of Philadelphia who were born in 1987-1997, were New Jersey residents, had their last primary care visit at age $12 years, and acquired a driver's license (N = 14 936). Electronic health records were link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…Thus, ADHD that is not identified or managed may lead to considerable consequences in daily activities. 3,4 Type 1 diabetes mellitus (T1DM) is one of the most common chronic diseases in childhood and adolescence. Despite the technological improvement in the treatment of T1DM over recent years, diabetes management remains intensive and very demanding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ADHD that is not identified or managed may lead to considerable consequences in daily activities. 3,4 Type 1 diabetes mellitus (T1DM) is one of the most common chronic diseases in childhood and adolescence. Despite the technological improvement in the treatment of T1DM over recent years, diabetes management remains intensive and very demanding.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired executive functioning is a major component of the clinical presentation of ADHD. Thus, ADHD that is not identified or managed may lead to considerable consequences in daily activities 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…However, their study group was restricted to adults. Adolescents tend to have more road safety problems, including risky driving behaviours, traffic violations and driving without a license (Dobhal et al ., 2019 ), especially for individuals with ADHD (Curry et al ., 2017 ; Curry et al ., 2019 ). Therefore, it is reasonable to include the adolescent population in the long-term study to explore the association between ADHD and vehicle accidents.…”
Section: Introductionmentioning
confidence: 99%
“…15 Studies have shown that drivers with ADHD, in addition to inattention glitches while driving, often exhibit inappropriate anger that may escalate into a road rage, therefore, increasing the risk of unsafe driving and higher rates of car crashes compared to a healthy population. 14,15,33,34 However, surprisingly, patients with ADHD were found to perform better at a hazardous situation than healthy controls in 1 study, a finding proposed to be related to the better engagement of the patient in the task at hand with a heightened task demand, but medicated drivers clearly performed better in terms of speed control and fewer driving errors than those with untreated ADHD. 35 Although the Swedish National Patient Register study 27 concluded that ADHD is the main factor in driving impairment among patients with TS, impulsivity, as illustrated in our patient in case 1, may also play a role.…”
Section: Discussionmentioning
confidence: 71%